Exercise-induced right ventricular alterations in a rodent model of athletes heart. (10th June 2022) - Olah, A; Bodi, B; Sayour, AA; Barta, BA; Ruppert, M; Bottlik, O; Merkely, B; Papp, Z; Radovits, T
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): János Bolyai Research Scholarship of the Hungarian Academy of Sciences (BO/00837/21) to AO National Research, Development and Innovation Office (NKFIH) of Hungary (K120277 and K135076 to BM) Background: Intense sports activity leads to the adaptation of cardiac structure and function, the so-called athlete's heart. Research over the last years has focused on exercise-induced adaptation of the right ventricle (RV), because the disproportionate load on the RV - when compared with left ventricle - might lead to pathological consequences, such as interstital fibrosis or chamber dilation. Purpose: We aimed at investigating right ventricular alterations induced by regular aerobic exercise training in a rat model of athlete's heart. Methods: Young, adult rats were divided into control (Co) and exercised (Ex) groups. Trained rats swam 200 min/day for 12 weeks. In vivo electrophysiological study and in vitro force measurements on isolated permeabilized cardiomyocytes were carried out to investigate electrical and functional alterations, respectively. Molecular biological (qRT-PCR, Western-blot) and histological investigations were applied to reveal underlying mechanisms. Results: Exercise training was associated with increased RV cardiomyocyte width (12.5±0.1µm Co vs. 13.8±0.2µm Ex, p<0.05) and corresponding hyperphosphorylation of protein kinase B (Akt). RV myofilaments from exercised animals showed increased maximal force development and improved calcium sensitivity. Sarcomere protein investigations revealed marked overall and site-specific hypophosphorylation of troponin I. We found prolonged QT interval and right ventricular effective refracter period (RVERP: 44.0±1.6ms Co vs. 52.8±2.1ms Ex, p<0.05) along with decreased gene expression of potassium channels. Picrosirius staining did not reveal fibrosis, that was underlied by unchanged protein expression of connective tissue growth factor (CTGF) and gene expression of profibrotic markers. Gene expression of apoptotic markers and fetal gene program did not differ between the groups. Conclusions: According to our data, regular swim training induced RV hypertrophy, that was associated with functional improvement adn hypophosphorilation of troponin I. Prolonged repolarization without pathological alterations in RV myocardial tissue suggest physiological remodeling after balanced training.